HIV Tat excites D1 receptor-like expressing neurons from rat nucleus accumbens - Brailoiu, G. Cristina (Drug Alcohol Depend, 2017)
BACKGROUND: HIV-1 infection and drug abuse are frequently co-morbid and their association greatly increases the severity of HIV-1-induced neuropathology. While nucleus accumbens (NAcc) function is severely perturbed by drugs of abuse, little is known about how HIV-1 infection affects NAcc. METHODS: We used calcium and voltage imaging to investigate the effect of HIV-1 trans-activator of transcription (Tat) on rat NAcc. Based on previous neuronal studies, we hypothesized that Tat modulates intracellular Ca(2+) homeostasis of NAcc neurons. RESULTS: We provide evidence that Tat triggers a Ca(2+) signaling cascade in NAcc medium spiny neurons (MSN) expressing D1-like dopamine receptors leading to neuronal depolarization. Firstly, Tat induced inositol 1,4,5-trisphsophate (IP(3)) receptor-mediated Ca(2+) release from endoplasmic reticulum, followed by Ca(2+) and Na(+) influx via transient receptor potential canonical channels. The influx of cations depolarizes the membrane promoting additional Ca(2+) entry through voltage-gated P/Q-type Ca(2+) channels and opening of tetrodotoxin-sensitive Na(+) channels. By activating this mechanism, Tat elicits a feed-forward depolarization increasing the excitability of D1-phosphatidylinositol-linked NAcc MSN. We previously found that cocaine targets NAcc neurons directly (independent of the inhibition of dopamine transporter) only when IP(3)-generating mechanisms are concomitantly initiated. When tested here, cocaine produced a dose-dependent potentiation of the effect of Tat on cytosolic Ca(2+). CONCLUSION: We describe for the first time a HIV-1 Tat-triggered Ca(2+) signaling in MSN of NAcc involving TRPC and depolarization and a potentiation of the effect of Tat by cocaine, which may be relevant for the reward axis in cocaine-abusing HIV-1-positive patients.